The perception of employees toward the user - friendliness of performance appraisal based on Sistem Saraan Malaysia (SSM) - Caroline, Hwang. (Universiti Malaysia Sarawak (UNIMAS), 2005)
This study aims to identify the perception of employees toward the user-friendliness of performance appraisal based on Sistem Saraan Malaysia (SSM). This study also determines the difference in the perception of employees toward the user-friendliness of the performance appraisal based on the SSM according to the chosen demographic characteristics. Apart from that the study also focusing on factors, that is the format, process and procedure and its relationship with the employee perception. Questionnaires have been used in collecting the data. The sample of the study is the employee in Universiti Malaysia Sarawak (Unimas). The finding of this study shows that there is a significant difference in the perception according to the chosen demographic characteristics. The study also found that 93.55 percents of employees have a positive perception towards the user-friendliness of the performance appraisal based on SSM. 3 factors that influence the perception"of employees also show a positive relationship the user-friendliness of the performance appraisal. Emphasis should be given to this 3 factor in determining the user-friendliness of the performance appraisal. As conclusion, there are many aspects that can influence the perception of employee towards the user friendliness of the performance appraisal. Therefore the government, organization and supervisor should take a necessary action and adopt with the needs of employee to make the performance appraisal user-friendly.